Vaccination against canine leishmaniasis in Brazil. Issue 3 (March 2020) - Dantas-Torres, Filipe; Nogueira, Fábio dos Santos; Menz, Ingrid; Tabanez, Paulo; da Silva, Sydnei Magno; Ribeiro, Vitor Márcio; Miró, Guadalupe; Cardoso, Luís; Petersen, Christine; Baneth, Gad; Oliva, Gaetano; Solano-Gallego, Laia; et al.
Graphical abstract: Highlights: Dogs play a key role in the transmission of Leishmania infantum to humans. Preventing L. infantum infection in dogs is pivotal from a one health perspective. A bill is currently proposing a canine leishmaniasis vaccination policy in Brazil. There is no solid scientific evidence supporting this proposal. Topically applied pyrethroids are recommended to prevent infection in dogs. Abstract: Prevention of canine Leishmania infantum infection is critical to management of visceral leishmaniasis in people living in endemic areas of Brazil. A bill (PL 1738/11), currently under consideration, proposes to establish a national vaccination policy against canine leishmaniasis in Brazil. However, there is no solid scientific evidence supporting the idea that this could reduce transmission from infected vaccinated dogs to sand flies to a level that would significantly reduce the risk of L. infantum infection or visceral leishmaniasis in humans. Thus, we advocate that insecticide-impregnated collars should the first line protective measure for public health purposes and that vaccines are applied on a case-by-case, optional basis for individual dog protection.